APLIKASI JUAL BELI SBSN (SUKUK NEGARA) SECARA LELANG DI INDONESIA - Susamto, Burhanuddin (Fakultas Ekonomi, UIN Maliki Malang, 2011)
In financial empowerment, the government needs to improve efficiency in the management of state assets through efforts to diversify sources of financing the national budget. Conventional financing instruments issued by governments are ever Government Securities (SUN). Such instruments are operated based on usury system (riba) that becomes its own expense for the state budget from year to year. Not to mention it is evaluated in terms of the transcendental, SUN based on usury means has violated religious teachings. Therefore, as an alternative effort, the government has elicits other financing instruments, such as through an auction sale (penjualan lelang) of the SBSN (Sovereign Sukuk) which has been published.